Analysis of Entropy Generation and Energy Transport of Cu-Water Nanoliquid in a Tilted Vertical Porous Annulus - Swamy, H. A. Kumara; Sankar, M.; Reddy, N. Keerthi (International journal of applied and computational mathematics, 2022)
The physical structure in several industrial applications which includes cooling of electronic equipment, heat exchangers, nuclear reactors, and solar collectors, could aptly represent the cylindrical annular porous geometry. The prior knowledge of buoyant flow and thermal transport rates in this geometry provides the vital information to the design engineers. In this article, we analyze the convective nanoliquid flow and associated thermal dissipation as well as entropy generation rates in an inclined annular enclosure filled with nanoliquid saturated porous medium. The vertical surfaces of inner and outer cylinders are maintained at uniform, but different temperatures and horizontal boundaries are kept insulated. The momentum equations are modeled utilizing the Darcy law, the coupled partial differential equations are numerically solved adopting the time splitting and line over relaxation techniques. For the numerical simulations, a vast range of parameters such as the Darcy Rayleigh number (10 ≤ R a D ≤ 10 3 ), annulus inclination angle (0° ≤ γ ≤ 60°), aspect ratio (0.5 ≤ Ar ≤ 2) and nanoparticle volume fraction (0 ≤ ϕ ≤ 0.05) are considered. The contributions of heat transfer and fluid friction entropies to global entropy production in the geometry are determined through the Bejan number. The numerical results reveal that the convective flow, heat transfer and entropy generation rates could be controlled with the aid of cavity inclination angle. It is found that the shallow annular enclosure gives better thermal performance with minimum entropy generation regardless of R a D , γ and ϕ . Further, the results are in excellent agreement with standard benchmark simulations. The predicted results could provide some vital information to enhance the system efficiency .